APLIKASI PEMETAAN PONDOK PESANTREN BERBASIS WEB DI KABUPATEN JOMBANG - Baharudin, Ilham; Sujatmiko, Bambang; Faizah, Arbiati (Inovate, 2019)
Jombang Regency is known as city of â€œsantriâ€ because there are many â€œpondok pesantrenâ€ which arefamous in Indonesia domiciled in this city. At least there are seven large â€œpondok pesantrenâ€ located inthe Jombang area. Apart from the strategic geographical location in the city of â€œsantriâ€, great figures wereborn, one of which was the forerunner of the resistance of the community and the â€œsantriâ€ towards theinvaders who were commanded by Hadratussyaikh KH.M Hasyim Asy'ari, the founder of Nahdlotul Ulamaand KH. A Wahid Hasyim, 4President is K.H Abdurrahman Wahid. Based on the description above, inorder to help parents who want to know the geographical location and the teaching system in â€œpondokpesantrenâ€ in Jombang, the application of mapping â€œpondok pesantrenâ€ is needed which can help parentsknow what kind of boarding school information is in Jombang Regency with 3 groups, namely there arePondok Pesantren Salaf, Pondok Pesantren Tahfidz, and Pondok Pesantren Modern and know thegeographical location of â€œpesantrenâ€ with website-based mapping visualization.Keywords: Jombang Regency, Pondok Pesantren, Mapping.th